The Effect of Peer Feedback Technique in Improving Students’ Writing Skill in Descriptive Text - SUAIB, SISKA; Suriaman, Aminah; Budi; Jamil, Jamiluddin (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The purpose of this research was to determine whether peer feedback techniques can improve students' writing skills at Man Insan Cendekia KOTA PALU. This research employed a quasi-experimental design, which consisted of two groups, namely the control group and the experimental group. Researchers gave pre-tests to determine the ability of the two groups before giving treatment. The pre-test result showed that the control group scored higher than the experimental group. Then, the researchers gave the treatment using peer feedback techniques in the learning process to the experimental group. Finally, researchers gave the post-test to both groups. The post-test result showed that the experimental group achieved higher scores compared to the control group. It is because of the use of peer feedback techniques that students can identify mistakes in their writing and receive suggestions from peers, so they are able to write texts well according to comments and suggestions from their friends. The results of the research show that the use of peer feedback techniques has a positive effect on improving students' writing skills at Man Insan Cendekia Kota Palu